Dance for negative symptoms in Autism Spectrum Disorder (ASD): a systematic review - Jesus, Beatriz Menezes de (2019)
Background: Autism spectrum disorder (ASD) is characterized as a neurodevelopmental disorder with stereotyped and repetitive behaviors. Dance practice is able to surface esthesia to awake the communication process, by the notion of the phenomenal body that is recognized in an expressive and symbolic space. Objective: To conduct a systematic review to identify how dance influences negative symptoms in ASD. Method: We formulated the research question based on PICO: “What is the influence of dance on negative symptoms in individuals with autism spectrum disorder?”. Included databases were PubMed, Science Direct, Scopus, PsycInfo and Web of Science and, which were searched in March 2019. Results: We identified 9.350 studies, and five were selected in our review (total of 266 individuals). All included studies showed dance influence on negative symptoms, including empathy, emotional expression, body awareness, behavior, and psychological wellbeing that 5 impact on social reciprocity, and consequently in communication process in ASD. Dance practice may contribute to body awareness and social involvement by techniques that provide mirrorring, syncronization, rhythm, and reciprocity in adults with ASD normal to high functioning.